Proses Pergantian Varietas Ubi Cilembu sebagai Bentuk Adaptasi Petani terhadap Penurunan Produksi Varietas Neerkom - Tanjung, Melbi (Jounal of Enviromental Science Sustainable, 2023)
Diversity sweet potato varieties in Cilembu is a form of adaptation of farmers in the face of declining productivity conditions Neerkom variety. This research was aimed to explain the process of turning from one variety to become diverse variety. This research had been done with qualitative method. The data were taken by an intensive interview with farmers, marketer, researcher, and agricultural agent from the Regency Agricultural Departement and also by doing field observation and documentation. The process of replacing Cilembu sweet potato varieties is as follows: Neerkom – Eno – Ubi-ubi Jepang (Murasaki, Beniazuma, Beniazma, Ibaraki) – Rancung – Jawer – Odos – Inul – Bagolo – Rancing. Farmers continue to make selection and adaptation, namely by developing other varieties that can replace the Neerkom variety in order to create sustainable agricultural development in Cilembu Village. Key words: Variety, Cilembu Sweet Potato, Adaptation, Sustainable Agriculture